Gender justice – a precondition for resilience - Bryan, Elizabeth; Meinzen-Dick, Ruth S.; Ringler, Claudia (2023)
Women and girls in poorer countries are affected in particular ways by the multiple crises the world is currently facing. Uncovering the linkages between gender, resilience and food security, our authors look at ways to support women and girls’ capacity to respond to crises and make them more resilient. They also explore what can be done to address underlying gender inequalities.